Early adolescent childbearing in Colombia: time-trends and consequences - Marta Cecilia Jaramillo-Mejía; Dov Chernichovsky (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Teenage childbearing has been increasing, especially among girls aged 10 to 14 years, slowing the improvements in public health and propelling social marginalization. The objective of this article is to study adolescent pregnancy in Colombia and suggest possible policy interventions. The study comprises univariate and multivariate analyses that examine trends and correlates of teenage childbirth and related infant mortality in Colombia between 2001-2011 using complete vital statistics. The study compares, by relative risk analysis as well, two groups of teenage mothers, aged 10 to 14 years and 15 to 19 years, with a reference group of mothers aged 20 to 34 years. During the study period, the average of annual birth rates increased 2.6% and 0.8% in mothers aged 10 to 14 years, and 15 to 19 years respectively, whereas it declined at an average rate of 0.2% annually for mothers aged 20 to 35 years. Simultaneously, while the overall rate declined, the infant mortality rate (IMR) of the youngest group was consistently higher during the entire period compared to the IMR of older groups. Compared with the other groups, mothers aged from 10 to 14 were more likely to be unmarried, rural, indigenous or afro-descendant, and have less access to health care. The study demonstrates that early teenage childbirth is a growing challenge at least in Colombia. These mothers are at higher risk of losing their babies while being poor and remaining poor. The study suggests the need for policy that targets appropriate education and health care to poor girls as early as age 10 and even younger.